Las políticas públicas que se han realizado como solución para el problema de violencia de género en México - Erazo Herdoíza, Thays Alejandra (2016)
Gender-based violence is a social problem for states, because in a society that can be described as "sexist" because it is expressed through a social construct imposed by the power of men over women in all bearings of life. That is why the State to have an essential duty to ensure human rights, should promote the creation of public policies for this problem levels are reduced if not eliminated. So by analyzing the theory of public choice, which explains the rational actions of individuals when making decisions through the power, must set priorities to solve problems within an economic logic, which should choose the general interest that maximizes welfare. So one could say that the pressure of organized citizens could lead us to the formation of public policies that address conflicts such as the violence against women, through concrete cycles construction of public policies through six steps, of which the most important is the evaluation of the results, which will verify their success and acceptance of citizenship. This analysis will also include aspects of design, content and results of public policies, in the case of Mexico and contrast with what has been achieved in Ecuador.